Non-contact Tomographic Imaging and Nanocomposite Thin Films for Monitoring Human-prosthesis Interfaces. (2017) - Gupta, Sumit; Loh, Kenneth J.
Abstract: The objective of this work is to develop a non-contact, non-invasive technique for monitoring human-prosthesis interfaces, such as the development of infection. The monitoring scheme proposed works by coupling electrical capacitance tomography (ECT) with a pH-sensitive nanocomposite thin film applied at the human-prosthesis interface. In short, ECT uses applied electrical excitations and measurements at the boundaries to reconstruct the spatial permittivity distribution inside the sensing region. The pH-sensitive nanocomposite pronounces permittivity changes due to issues occurring at the human-prosthesis interface, thereby enhancing detection sensitivity and resolution. First, numerical simulations were performed by altering the permittivity at selected locations in a mathematical model to simulate the effect of infections near a prosthesis. The extent and shape of the perturbed permittivity was captured by numerical simulations of ECT. Second, experiments were conducted in the laboratory to validate the monitoring system and sensing scheme. Here, a pH-sensitive thin film was fabricated using carbon nanotubes and polyaniline. The thin film's pH sensitivity was characterized by exposing it to different pH buffer solutions and measuring its corresponding dielectric property changes. A circular plastic rod was then used as a phantom for a human prosthesis, for example, to simulate the portion of an artificial limb that would be embedded in and bonded to the human body. The thin film was then deposited onto the surface of the prosthetic phantom and exposed to different pH buffer solutions. For each case, the ECT monitoring system was used to interrogate the prosthetic phantom placed in the sensing area. Not only did the system detect changes in permittivity due to different pH buffers, but the reconstructed permittivity maps also identified the location of the permittivity changes, as well as the prosthesis itself.